2019
DOI: 10.1063/1.5084052
|View full text |Cite
|
Sign up to set email alerts
|

Electron scattering in quantum waveguides with sources and absorbers. I. Theoretical formalism

Abstract: We develop a novel method based on sources and absorbers to examine quantum scattering in finite, nanoscale systems. We show that the Cauchy (mixed) boundary conditions (BCs) are required to put the scattering theory into an action integral formulation. These complex BCs are reduced to simpler Dirichlet BCs by introducing totally absorbing “stealth regions.” Material properties of these enclosing regions are optimized to give decaying solutions so that the scattering amplitudes vanish at the finite boundaries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Previously, for electron scattering in waveguides, we proposed a method to reduce the scattering BCs to Dirichlet BCs by creating absorbers (stealth regions) on either end of the waveguide [28]. An extension of this technique to 2D open domain is achieved here by creating circular absorbers around the scattering center, as shown in Fig.…”
Section: Planewave Sourcementioning
confidence: 99%
See 4 more Smart Citations
“…Previously, for electron scattering in waveguides, we proposed a method to reduce the scattering BCs to Dirichlet BCs by creating absorbers (stealth regions) on either end of the waveguide [28]. An extension of this technique to 2D open domain is achieved here by creating circular absorbers around the scattering center, as shown in Fig.…”
Section: Planewave Sourcementioning
confidence: 99%
“…Here, α(r) is the cubic Hermite interpolation polynomial varying smoothly from 0 to α max . Through such transformation, it has been shown that the no-reflection condition is satisfied [28] and the absorber will not reflect any wave back into the active region confined within the absorber. Therefore, scattering properties in the active region remain unaffected by the presence of the absorber.…”
Section: Planewave Sourcementioning
confidence: 99%
See 3 more Smart Citations